Ionic Regulation of Cell Volume Changes and Cell Death after Ischemic Stroke - Song, Mingke (2013)
Stroke is a leading cause of human death and disability in the US and around the world. Shortly after the cerebral ischemia, cell swelling is the earliest morphological change in injured neuronal, glial and endothelial cells. Cytotoxic swelling directly results from increased Na(+) (with H(2)O) and Ca(2+) influx into cells via ionic mechanisms evoked by membrane depolarization and a number of harmful factors such as glutamate accumulation and the production of oxygen reactive species (ROS). During the sub-acute and chronic phases after ischemia, injured cells may show a phenotype of cell shrinkage due to complex processes involving membrane receptors/channels and programmed cell death signals. This review will introduce some progress in the understanding of the regulation of pathological cell volume changes and the involved receptors and channels, including NMDA and AMPA receptors, acid-sensing ion channels (ASIC), hemichannels, transient receptor potential (TRP) channels and KCNQ channels. Moreover, accumulating evidence supports a key role of energy deficiency and dysfunction of Na(+)/K(+)-ATPase in ischemia-induced cell volume changes and cell death. Specifically, the Na(+) pump failure is a prerequisite for disruption of ionic homeostasis including a pro-apoptotic disruption of the K(+) homeostasis. Finally, we will introduce the concept of hybrid cell death as a result of the Na(+) pump failure in cultured cells and the ischemic brain. The goal of this review is to outline recent understanding of the ionic mechanism of ischemic cytoxicity and suggest innovative ideas for future translational research.